Distributed Active-Passive Reconfigurable Intelligent Surface Assisted MISO Secure Communications - Yi Peng; Yu Zhang; Qingqing Yang; Jian Tang; Jianming Wang; Hui Li (IEEE Access, 2024)
This paper addresses the secure communication problem in a distributed active-passive reconfigurable intelligent surface (RIS) assisted multiple-input single-output (MISO) scenario with a single-antenna malicious eavesdropper. The objective is to maximize the secrecy rate of the single-antenna legitimate user under constraints on the base station (BS) power and RIS amplification coefficients. The study investigates a joint optimization algorithm for BS beamforming and RIS phase-shift matrices. To address the complex non-convex fractional programming problem with coupled variables, an alternating optimization (AO) algorithm based on semi-definite relaxation (SDR) and the method of minorization maximization (MM) is proposed to obtain a suboptimal solution to the optimization problem. Simulation results demonstrate that the proposed AO algorithm achieves better secrecy performance with fewer iterations compared to traditional approaches. The design of the distributed active-passive RIS effectively mitigates the “double fading” effect, leading to a significant improvement in secrecy rate compared to existing active RIS and passive RIS designs.